2008
DOI: 10.1016/j.jcrs.2008.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene suture–guided valve tube for posterior chamber implantation in patients with pseudophakic glaucoma

Abstract: We describe a new surgical procedure for implanting a glaucoma drainage tube in the posterior chamber. A needle with a 10-0 polypropylene suture is introduced into the posterior chamber, and a 23-gauge needle is also introduced as the barrel on the polypropylene needle tip. After the 23-gauge needle is withdrawn from the posterior chamber, the polypropylene needle tip is pulled and the suture crosses the anterior and posterior chambers. A sliding knot is made around the drainage tube. The tube is pushed into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Asaoka et al reported that 42/91 eyes (46%) were not successfully placed to ciliary sulcus with a single attempt, and 4/91 eyes (4.4%) were unable to achieve ciliary sulcus insertion [3]. A technique for ciliary sulcus insertion has been reported using 10-0 nylon thread with straight needle to create a sliding knot, but the technique is complicated [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asaoka et al reported that 42/91 eyes (46%) were not successfully placed to ciliary sulcus with a single attempt, and 4/91 eyes (4.4%) were unable to achieve ciliary sulcus insertion [3]. A technique for ciliary sulcus insertion has been reported using 10-0 nylon thread with straight needle to create a sliding knot, but the technique is complicated [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the low rigidity of AGV tube causes difficulties in insertion to ciliary sulcus, such as straying into the vitreous cavity or into an unidentifiable position, when using simple insertion methods [3]. Several techniques have been reported to overcome these problems, although problems remain, such as the complexity and unreliability of the procedure, and costs of the materials used [4][5][6][7][8]. In this study, we report a simple and precise technique of AGV tube insertion into the ciliary sulcus using inexpensive 4-0 nylon thread as a guide.…”
Section: Introductionmentioning
confidence: 99%
“…Even though, the use of a 21G needle (outer diameter of 0.81 mm) for the ab interno tube insertion is wider than a 23G needle (outer diameter 0.64 mm) which is commonly used by other authors, it appears to be safe and may not necessarily imply a higher risk. 9,12,15,19…”
Section: Discussionmentioning
confidence: 99%
“…The current technique is easy to perform; the tube is inserted adequately behind the iris but remains visible through the pupil and is a safe distance from the cornea. We have performed other surgical approaches to insert the tube into the posterior chamber, but in our hands, the current technique is the simplest of all the approaches to achieve that end [6]. Our surgical procedure has other potential advantages in that it can be performed with different GDDs with a 23gauge tube (Ahmed or Baerveldt), it can be performed simultaneously with cataract surgery or penetrating keratoplasty or Descemet membrane endothelial keratoplasty (DMEK), or to change the tube from the anterior to the posterior chamber in cases with rapid endothelial cell loss.…”
Section: Discussionmentioning
confidence: 99%